Class Action Lawsuits as a Mechanism of Civil Liability in Environmental Disputes - Helidorus Chandera (Rechtsvinding, 2026)
This article examines class action lawsuits as a mechanism of civil liability in environmental disputes within the framework of environmental civil law. Environmental degradation and pollution often cause widespread and diffuse harm, affecting large groups of people whose individual losses are difficult to quantify and whose access to justice is frequently constrained by procedural and economic barriers. Against this background, the study aims to analyze the role of class action litigation in ensuring effective protection of victims’ civil rights and promoting environmental restoration through private law remedies. The research adopts a normative juridical method, combining statutory analysis of environmental legislation and civil liability doctrines with a conceptual approach to class action procedures, including principles of standing, representation, and remedies. The article finds that class action lawsuits function as an important procedural tool to operationalize civil liability in environmental disputes, particularly in addressing collective losses, enforcing strict liability, and facilitating compensation and environmental remediation. Class actions also strengthen access to justice by reducing litigation costs, balancing the power asymmetry between victims and corporate polluters, and enhancing the deterrent effect of civil liability without relying on criminal sanctions. However, their effectiveness depends on clear legal standards for group representation, proof of causation, and the formulation of restorative remedies. The study concludes that class action litigation should be further developed and consistently applied as a core civil law mechanism in environmental dispute resolution, as it aligns with the objectives of environmental protection, victim-oriented justice, and sustainable environmental governance.